Vegetation analysis of the Forest Park of Pocut Meurah Intan (THRPMI), Seulawah Subdistrict, Aceh Besar, Aceh Province. Issue 1 (January 2022) - Djufri, D; Hasanuddin, H; Abdullah, A; Puspa, V R
Abstract: A study entitled "Vegetation Analysis of the Forest Park of Pocut Meurah Intan, Seulawah Subdistrict of Aceh Besar, Aceh Province" has been conducted since April 2019 until November 2019. A transect method and squares were used in this study. The transect method was used to record species composition throughout the observation stations (inventory of species), including stands of pine (Pinus merkusii) with ten stations transect, stands of eucalyptus (Eucalyptus urophylla), stands of cacao (Theobroma cacao), and natural forests within a radius of 2 km around the THRPMI office. The squares method was used to record the species in the same locations to replicate each station by ten squares of samples for vegetation analysis. The parameters measured in the field were frequency, density, and dominance of each species. Analysis of vegetation covered Importance Values (IV), Diversity Index (H '), and the Similarity Index (SI). Results showed that there were 49 familia found with the composition of species in the entire observation stations comprising of 111 species with 58 species of trees, 12 species of shrubs, and 41 species of herbs. Additionally, the results showed that the species of vegetation with the highest IV were coarse grass (Imperata cylindrica), lawn pait (Axonopus compresus), and selasi (Vernonia cinerea) with IV of 72.01, 65.34, and 57.24, respectively. Results of analysis Species Diversity Index (H ') showed that the Pinus merkusii had H' of 2, 134, whereas Eucalyptus urophylla had H 'of 1.965, and Theobroma cacao had H' of 1, 067. The results of the analysis of Community Similarity Index showed that all stations had the same relative SI of 75%. It can be concluded that the species composition of the study area dominated by tree species, species diversity index (H ') in all observation stations varied ranging from 1.067 to 2.134, and the relative Community Similarity Index was 75%.